The Making of Geographies: Exploring Integral Territory and Memory within Indigenous Protest - Ramos, Carola (2018)
The study of the relation between memory and geography has been mainly focused on the role of the built space (e.g. museums, monuments, heritage sites, and artifacts) with the production of sites of memorialization, as well as the use of space through performance or rituals in (re)creating memories or counter-memories by social groups. The reconstruction and recovering of an 'integral territory' among Amazonian peoples, which they describe as their ancestral way of living, is today also a modern project to define and reassert the control of their territories. In the light of a critical review of the literature on memory in geography and narrative analysis of interviews and documents elaborated by indigenous groups, I propose a conceptual framework to study the so-called anti-neoliberal protests of 2008-2009 in the Peruvian Amazon drawing on collective memory and decolonial theories.